Sexual harassment - ACTT poster, c 1985 (London, 1985)
1985 1980-95 "Sexual harassment - ACTT poster, c 1985" [BW0218], 1985, Trades Union Congress Poster published by the Association of Cinematograph, Television and Allied Technicians with a cartoon by Christine Roche.